Vaginal Bipolar Radiofrequency Treatment of Mild SUI: A Pilot Retrospective Study - Paolo Mezzana; Ignacio Garibay; Irene Fusco (Medicina, 2022)
Background and Objectives: This retrospective study investigates the action of a bipolar, temperature controlled, endovaginal RF handpiece for the treatment of mild, moderate, and severe stress urinary incontinence with a minimally invasive approach. Stress urinary incontinence (SUI) is a common condition resulting in involuntary urine leakage, with an associated social and psychological impact. SUI is the most common type of urinary incontinence in women. Materials and Methods: We retrospectively studied 54 patients for this study. The bipolar radiofrequency energy used in all patients was 50 W, with temperatures maintained between 41 °C and 44 °C. Two sessions were performed four weeks apart. In order to monitor all patients before the first treatment and 4 months after the second treatment, the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) was used. Paired Student’s t test was used to elaborate the statistical data. Results: The average frequency of urine leak improved from “2–3 times a week” (2.1 ± 1.3 points before the treatment) to “once a week” (0.8 ± 1.3 points 4 MFU post-treatment). The average volume improved from “small/moderate quantity” (3.2 ± 1.6 points before the treatment) to “none” (0.9 ± 1.4 points 4 MFU post-treatment). No adverse events or side effects were found. Conclusion: Our preliminary results represent a good starting point to check the effectiveness and validity of the bipolar radiofrequency temperature-controlled method in the treatment of SUI.